A Short Course of Economics - Blake, David; illustrated by Boey, Stephanie (London McGraw-Hill, 1993)
This new text is designed to give the reader a good understanding of the essentials of economics in a concise form. Although concise, it still analyzes some of the most sophisticated and up-to-date ideas and issues in the field, including interest rate volatility, contestable markets and the EMS. The text is divided into three sections - microeconomics; national macroeconomics; and international macroeconomics. It should be suitable for introductory courses in economics at all levels and ideal for modular courses, courses with a business or financial emphasis, MBA courses and professional training programmes. The models basic to economic analysis are clearly presented and a generous use of diagrams assists the explanations. Another feature is the specially prepared "Business Application" boxes. Each section of the text has three boxed discussions looking at such themes as the state of the property market, company borrowing and the effects of the exchange rate on company performance. In addition end-of-chapter summary sections and exercises are included to aid student understanding.
Includes Colored Ilustrarions and Index.
Keywords: Economics